The first probe of a FLASH proton beam by PET - Abouzahr, Firas; Cesar, J. P.; Crespo, P.; Gajda, M.; Hu, Z.; Klein, K.; Kuo, A. S.; Majewski, S.; Mawlawi, O.; Morozov, A.; Ojha, A.; Poenisch, F.; et al. (Physics in medicine and biology, 2023)
The recently observed FLASH effect related to high doses delivered with high rates has the potential to revolutionize radiation cancer therapy if promising results are confirmed and an underlying mechanism understood. Comprehensive measurements are essential to elucidate the phenomenon. We report the first-ever demonstration of measurements of successive in-spill and post-spill emissions of gammas arising from irradiations by a FLASH proton beam. A small positron emission tomography (PET) system was exposed in an ocular beam of the Proton Therapy Center at MD Anderson Cancer Center to view phantoms irradiated by 3.5 × 1010 protons with a kinetic energy of 75.8 MeV delivered in 101.5 ms-long spills yielding a dose rate of 164 Gy s−1. Most in-spill events were due to prompt gammas. Reconstructed post-spill tomographic events, recorded for up to 20 min, yielded quantitative imaging and dosimetric information. These findings open a new and novel modality for imaging and monitoring of FLASH proton therapy exploiting in-spill prompt gamma imaging followed by post-spill PET imaging.
Gesehen am 26.01.2024